Advanced stage cervical carcinoma diagnosed one year after pregnancy: the importance of cervical cancer screening - Çelik, Gayem Inayet; Akpak, Yasam Kemal; Kantarci, Sercan; Karabulut, Alaattin; Oral, Serkan (International Journal of Scientific Reports, 2021)
Cervical cancer is the most common gynecological malignancy during pregnancy. The incidence of cervical cancer during pregnancy is 0.004-0.1%. Cervical cancer accompanied by pregnancy may have severe maternal and fetal consequences. In our case, our patient died approximately 1 year after giving birth and 2 months after being diagnosed with cervical cancer. Among the treatment options, chemotherapy, radiotherapy and surgical treatment options were available alone or in combination. Type of treatment needed to be individualized and depended on stage, type of histology and gestational age. The aim of our study was to emphasize the importance of vaginal examination and its method during pregnancy in the diagnosis of cervical cancer, which was among the preventable cancers in pregnancy.